Dinamika Ibadah dalam Kehidupan Umat Allah hingga Gereja Masa Kini - Mariani Harmadi; Tomson Lumban Tobing (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2021)
A problematic issue examined in this research, namely the vulnerability to unity and harmony in a church that consists of various members of its congregation. This condition is like bananas which differ from one another and are irregular in shape, so as to compose them requires a challenging effort and a long struggle. Lord Jesus prayed for the unity of believers, because this is essential for the expansion of the kingdom of God. As for goals, this research is to find the extent to which the effectiveness of the role of worship in the church to realize harmony among the various diversity including the differences in generations in the midst of a congregation, each of which is influenced by the style of music that develops in its day, where the phenomenon of movement of church members that occurs is caused by differences in musical tastes in worship, so as to answer this, research question is used descriptive qualitative method by examining the essence of worship, unity and diversity of historical, etymological, biblical and systematic angles. The conclusions obtained from these careful results, is that the worship that God has planned for His chosen people, including believers in the present and in the future, which contains a relationship that aims to strengthen the relationship for the realization of unity both the relationship between man and God, human and himself, as well as humans with each other in the midst of diversity towards harmony as Christian witness in the midst of the darkness of the world.